2016
DOI: 10.1097/dcr.0000000000000533
|View full text |Cite
|
Sign up to set email alerts
|

Medically Treated Diverticular Abscess Associated With High Risk of Recurrence and Disease Complications

Abstract: Diverticular abscesses represent complicated diverticulitis and are associated with a high risk of recurrences and disease complications. Recurrences (contrary to other series) were often more severe than the index presentation. The successful CT-guided drainage of a diverticular abscess does not appear to lower the risks of future recurrence or complication rates and frequently is only a bridge to surgery. After initial successful nonoperative management, patients with diverticular abscess should be offered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 26 publications
0
36
0
9
Order By: Relevance
“…Whilst our study suggests that elective colectomy may be over-utilized in some countries, its exact role remains controversial. The risk of recurrence after nonoperative management of diverticular abscess was found to be 61% in a study from the USA, suggesting a role for routine elective colectomy for these patients [26]. On the contrary, another study from New Zealand found a recurrence rate of 29% in similar patients, most of whom were managed nonoperatively [27].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst our study suggests that elective colectomy may be over-utilized in some countries, its exact role remains controversial. The risk of recurrence after nonoperative management of diverticular abscess was found to be 61% in a study from the USA, suggesting a role for routine elective colectomy for these patients [26]. On the contrary, another study from New Zealand found a recurrence rate of 29% in similar patients, most of whom were managed nonoperatively [27].…”
Section: Discussionmentioning
confidence: 99%
“…We did not consider factors such as body mass index, smoking or alcohol consumption, diet or the use of non‐steroidal anti‐inflammatory drugs in our analysis. However, some recent studies, including systematic reviews and meta‐analyses, agreed that AD recurrence (not the primary attack) was mainly influenced by young age, primary diverticulitis with abscess formation and prior episodes of AD, factors of which were all included in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, up to 25% of these patients will experience the recurrence of AD, which further increases the medical costs and morbidities related to this condition. Among these cases, young age and the presence of diverticular abscesses have been suggested as risk factors related to disease recurrence . Several drugs, such as rifaximin, have been investigated in the hope of reducing the incidence of recurrent diverticulitis; however, their effects may be limited and their efficacy remains controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients with a complicated initial presentation are more likely to have a second episode. In one series of 210 patients with a diverticular abscess, 60% had a second presentation that was frequently more severe than the initial presentation; 59% of these patients required surgery [15]. Furthermore, uncomplicated diverticulitis may not run a benign self-limiting course; up to 30% of patients without further episodes have ongoing abdominal symptoms labelled "smouldering" diverticulitis [16].…”
Section: Introductionmentioning
confidence: 99%